2005
DOI: 10.1074/jbc.m503638200
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Selenoprotein Thioredoxin-glutathione Reductase

Abstract: Thioredoxin reductases (TRs) are important redox regulatory enzymes, which control the redox state of thioredoxins. Mammals have cytosolic and mitochondrial TRs, which contain an essential selenocysteine residue and reduce cytosolic and mitochondrial thioredoxins. In addition, thioredoxin/glutathione reductase (TGR) was identified, which is a fusion of an N-terminal glutaredoxin domain and the TR module. Here we show that TGR is expressed at low levels in various tissues but accumulates in testes after puberty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(68 citation statements)
references
References 40 publications
2
61
0
5
Order By: Relevance
“…Functional analysis performed on SmTGR and on different TGRs proved that the penultimate Sec is essential for the reduction of thioredoxin and the glutaredoxin domain (6,12,15). Reduction of glutathione under physiological conditions is probably dependent on the redox exchange with glutaredoxin and thus is also inhibited in Sec-lacking enzymes, even though we observed residual GR activity in a C-terminally truncated variant of SmTGR (17).…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Functional analysis performed on SmTGR and on different TGRs proved that the penultimate Sec is essential for the reduction of thioredoxin and the glutaredoxin domain (6,12,15). Reduction of glutathione under physiological conditions is probably dependent on the redox exchange with glutaredoxin and thus is also inhibited in Sec-lacking enzymes, even though we observed residual GR activity in a C-terminally truncated variant of SmTGR (17).…”
mentioning
confidence: 66%
“…Characterization of mouse TGR demonstrated that the enzyme can reduce components of both mammalian Trx and GSH systems. In mammals, TGR exerts a wide range of catalytic activities though its selective overexpression in testis after puberty suggests its involvement in very specific functions related with sperm maturation (12).…”
mentioning
confidence: 99%
“…73 However, the physiological role that TrxRs play in the reduction of most of these substrates is still unknown. Some of the most likely functions for TrxRs are summarized in Fig.…”
Section: Thioredoxin Reductasesmentioning
confidence: 99%
“…This enzyme is mainly expressed in the male germ cells and has been suggested to play a role in sperm maturation by influencing the formation of disulfide bonds in structural proteins. 73 …”
Section: Thioredoxin Reductasesmentioning
confidence: 99%
“…Two redox-related proteins, glutathione peroxidase 4 and thioredoxin-glutathione reductase, have been studied extensively in association with spermiogenesis (17,18,25). Glutathione peroxidase 4 is highly expressed in spermatogenic cells and becomes oxidatively cross-linked to structural components of the sperm midpiece during spermiogenesis (18).…”
Section: Cellular Localization Of Prx Iv-s and Prx Iv-l In Mousementioning
confidence: 99%